What Drives the Innovation Inside, and Integrated Supply Chains of Thai Based Global Traders: A Strategic Management Perspective on Supply Chain Performance - Luedech Girdwichai; Jetsalid Anesukanjanakul; Komkrit Rattamanee; Vanisa Pakvichai (International Journal of Supply Chain Management, 2019)
The main objective of the current study is the enhancement in literature of SC with untying the association between SC practices, the innovation in CHIN and strategy orientation. SC practices have positive impact of Market orientation. Results are consistent with results of past studies of SC practices development achievement with the use of Market orientation. Contradiction with expectation information reveals that SC practices was not significant and positively related with resource orientation. According the study, a high level of investment for example in IT sector will not be beneficial for supply chain management. This suggestion indicates that managers should not make the excessive investment but have to allocate the resources of organization efficiently. The study has employed the SEM-PLS as a statistical tool to analyze the data collected from the Thai based global firms This study contributed in three aspects of supply chain management. First one is in, integration innovation, strategic management and SCM mainly the use of cross-disciplinary research. Previous studies have presumed that there is positive association among SCPR and innovation in CHIN. Though explanations regarding drivers of innovation in CHIN matters in association not been provided. Whereas we have provided new viewpoint for the explanation how sustained competitive advantage can be created for the firms by innovation in CHIN